Conjugate Ionospheric Perturbation During the 2017 Solar Eclipse. Issue 2 (10th February 2021) - Zhang, Shun‐Rong; Erickson, Philip J.; Vierinen, Juha; Aa, Ercha; Rideout, William; Coster, Anthea J.; Goncharenko, Larisa P.
Abstract: We report new findings of total electron content (TEC) perturbations in the southern hemisphere at conjugate locations to the northern eclipse on August 21, 2017. We identified a persistent conjugate TEC depletion by 10%–15% during the eclipse time, elongating along magnetic latitudes with at least ∼5° latitudinal width. As the Moon's shadow swept southward, this conjugate depletion moved northward and became most pronounced at lower magnetic latitudes (>−20°N). This depletion was coincident with a weakening of the southern crest of the equatorial ionization anomaly (EIA), while the northern EIA crest stayed almost undisturbed or was slightly enhanced. We suggest these conjugate perturbations were associated with dramatic eclipse initiated plasma pressure reductions in the flux tubes, with a large portion of shorter tubes located at low latitudes underneath the Moon's shadow. These short L‐shell tubes intersect with the F region ionosphere at low and equatorial latitudes. The plasma pressure gradient was markedly skewed northward in the flux tubes at low and equatorial latitudes, as was the neutral pressure. These effects caused a general northward motion tendency for plasma within the flux tubes, and inhibited normal southward diffusion of equatorial fountain plasma into the southern EIA region. We also identified posteclipse ionospheric disturbances likely associated with the global propagation of eclipse‐induced traveling atmospheric disturbances in alignment with the Moon's shadow moving direction. Plain Language Summary: A solar eclipse casts a supersonic moving shadow on Earth's atmosphere and impacts the upper atmosphere by masking solar irradiation. For a given location, this results in local reduction and recovery of photo‐ionization and photo‐absorption within ∼2 h. However, on a much larger scale, the moving, eclipse induced EUV screening lasting for multiple hours drives dynamical ionospheric variations. A global perspective on the eclipse induced ionospheric perturbation is now possible due primarily to the availability of total electron content (TEC) worldwide data from Global Navigation Satellite System (GNSS) receiver coverage. This paper reports new findings on total electron content perturbations in the southern hemisphere conjugate to the northern eclipse on August 21, 2017. While the moving Moon shadow was expected to yield traveling atmospheric disturbances, observational signatures of posteclipse traveling ionospheric disturbances propagating into the southern hemisphere were identified. Significantly, a persistent TEC depletion zone conjugate to the eclipse region occurred, elongated along magnetic latitudes with ∼5° latitudinal width, moving equatorward and most pronounced at lower magnetic latitudes (∼ −20°N and equatorward). This depletion was coincident with a weakening southern equatorial ionization anomaly (EIA) while the northern EIA remained unaffected or was slightly enhanced. We suggest that both conjugate density depletion and disappearance of the southern EIA were associated with dramatic plasma pressure reduction in the magnetic field flux tubes, which are short in length at low latitudes and traverse the ionospheric F region when being shadowed by the Moon for a significant time. The plasma pressure gradient was skewed northward at low and equatorial latitudes, and neutral pressure gradients followed suit. Ultimately, these effects drove an overall northward motion of plasma in the flux tubes, inhibiting the normal southward diffusion of equatorial fountain plasma into the southern EIA region. Key Points: Persistent ionospheric density depletion in conjugate lower latitudes was identified during August 21, 2017 Solar Eclipse Conjugate depletion moved equatorward with eclipse progression and was coincident with weakening conjugate/southern equatorial ionization anomaly Plasma pressure reduction in flux tubes shadowed by the Moon, along with disturbed northward trans‐equator winds, prohibits fountain plasma southward diffusion